2017
DOI: 10.1039/c7ra04587e
|View full text |Cite
|
Sign up to set email alerts
|

In situ ATR-FTIR investigation and theoretical calculation of the interactions of chromate and citrate on the surface of haematite (α-Fe2O3)

Abstract: In situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy was used to study the molecular kinetics of Cr(VI) reduction by citric acid at the a-Fe 2 O 3 -water interface. Both citrate and Cr(VI) were adsorbed to the surface of a-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…This result contradicted the findings of previous studies, which implied that the IS complex formed mainly at low pH, whereas the outer-sphere complex was dominant at high pH. Gao et al (2017) tried to evaluate the interaction between citrate and chromate on hematite, and they observed the reduction of chromate to chromite by electron transfer from citrate. The structural configuration of citrate was presumed to be a monodentate or bidentate ring structure, but no detailed description was provided.…”
Section: Structural Configuration Of Organic Acidscontrasting
confidence: 81%
“…This result contradicted the findings of previous studies, which implied that the IS complex formed mainly at low pH, whereas the outer-sphere complex was dominant at high pH. Gao et al (2017) tried to evaluate the interaction between citrate and chromate on hematite, and they observed the reduction of chromate to chromite by electron transfer from citrate. The structural configuration of citrate was presumed to be a monodentate or bidentate ring structure, but no detailed description was provided.…”
Section: Structural Configuration Of Organic Acidscontrasting
confidence: 81%
“…Infrared (IR) studies of phosphate adsorption onto Fe‐oxides have shown that phosphate forms a mixture of different inner‐sphere surface complexes whose proportions vary with pH and surface coverage (Arai & Sparks, ; Elzinga & Kretzschmar, ; Elzinga & Sparks, ; Kubicki et al., ; Luengo, Brigante, Antelo, & Avena, ; Tejedor‐Tejedor & Anderson, ). The speciation of citrate at goethite and hematite surfaces is similarly complex and also consists of various complexes with variable abundance depending on pH and surface loading (Borer & Hug, ; Gao, Liu, & Chen, ; Lindegren & Persson, ; Lindegren, Loring, & Persson, ; Noerpel & Lenhart, ; Situm, Rahman, Goldberg, & Al‐Abadleh, ). The mechanistic complexity of phosphate and citrate adsorption makes it difficult to predict the behavior of these species in environments where both are present, highlighting the need for spectroscopic studies of dual‐sorbate systems.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the absorbance of the shoulder peak at 1531 cm –1 exhibited a distinct decrease compared with that of the CA-Sch system, indicating the reduction of coordinated carboxylate groups. , This phenomenon might be attributed to the weakening of one coordinated carboxylate group under the effects of Cr­(VI) adsorption. Gao et al found that electrons could be transferred from the carboxyl groups of CA to Cr­(VI) via the Fe–O bond of hematite. Therefore, redox reactions may occur between the coordinated CA and Cr­(VI) on the mineral surface, which will lead to the destruction of the surface geometry and produce changes in the bands of the IR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Citric acid (CA) is widely detected in acidic soil, sediment, and aquatic systems and commonly ranges from 0.01 to 1 mM . As well known, CA has three carboxyl groups, giving great complexation ability with iron oxides and forming inner or outer sphere complexes. , Meanwhile, CA could also act as a potential reductant for Cr­(VI) in the presence of iron and manganese oxides or titanium oxides. For example, Gao et al observed that the competitive adsorption and redox reactions both occurred between CA and Cr­(VI) on the hematite surface. Jiang et al found that Cr­(VI) could be reduced by CA over Sch in a homogeneous system under mimic solar light, which was prevalent in naturally contaminated environments.…”
Section: Introductionmentioning
confidence: 99%